The Relationship between Currency Conversions and International Business Transactions: Small Businesses and Travelers - Oriaku, Ngozi; Oriaku, Ebere (The Economics and Finance Letters, 2016)
This research looks at currency conversions and how it affects international business transactions especially small businesses and travelers. The idea is to show the discrepancy of currency conversion and the factors that do affect currency conversion in any given time for a business person or a traveler. In order to increase small business and traveler’s awareness when it comes to doing business abroad, it is imperative to understand the currency conversions, its implications, and the commitments needed to protect investments and value of the conversion exchange. Research shows that small businesses have little or no adequate knowledge of currency conversions. The paper research questions are: (1) Do foreign exchange rates uncertainty reduce the incentive of travelers and small business owners from transacting business abroad? (2) Is it necessary for travelers and small business owners to understand the relevance of foreign exchange rates and risks management?